Measurement of the D*± cross section in two photon collisions at LEP - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1995)
The inclusive production of D∗± mesons in photon-photon collisions has been measured by the Aleph experiment at LEP with a beam energy of 45 GeV. The D∗+ are detected in their decay to D0π+ with the D0 observed in three separate decay modes: (1) K−π+, (2) K−π+π0 and (3) K−π+π−π+, and analagously for the D∗− modes. A total of 33 events was observed from an integrated luminosity of 73 pb−1 which corresponds to a cross section for Σ(e+e−→ e+e−D∗±X) of 155 ± 33 ± 21 pb. This result is compatible with both the direct production γγ → cc in the Born approximation and with a more complete calculation which includes both radiative QCD corrections and contributions in which one of the photons is first resolved into its quark and gluon constituents. The shapes of distributions for events containing a D∗+ are found to be better described by the latter.